2007
DOI: 10.3349/ymj.2007.48.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Gasless Endoscopic Thyroidectomy via an Anterior Chest Wall Approach Using a Flap-Lifting System

Abstract: PurposeEndoscopic thyroidectomy (ET) requires a proper working space for adequate visualization of anatomical structures and proper instrument manipulation. The purpose of this prospective study was to estimate the feasibility and safety of ET using an anterior chest wall approach without gas insufflation.Materials and MethodsThe working space was created under a direct and endoscopic view through a 3-cm incision on the anterior chest wall. A retracting device was then inserted to establish the working space, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 12 publications
(16 reference statements)
0
35
1
2
Order By: Relevance
“…Arterial and venous injuriesprobably due to inadequate experience with the endoscopic instrumentation-can occur. Other complications common to all thyroid surgery have been reported, such as hypocalcemia, recurrent laryngeal nerve palsy, seroma, hematoma, and postoperative infection [33,38,39,49,50]. The most severe complications were observed mainly in the first attempts of endoscopic surgery [4], while newer studies have revealed milder or even no complications [17,[39][40][41][42][43].…”
Section: Complicationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Arterial and venous injuriesprobably due to inadequate experience with the endoscopic instrumentation-can occur. Other complications common to all thyroid surgery have been reported, such as hypocalcemia, recurrent laryngeal nerve palsy, seroma, hematoma, and postoperative infection [33,38,39,49,50]. The most severe complications were observed mainly in the first attempts of endoscopic surgery [4], while newer studies have revealed milder or even no complications [17,[39][40][41][42][43].…”
Section: Complicationsmentioning
confidence: 96%
“…The applications of these approaches are summarized in Table 1 [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. With these new techniques the scars are not necessarily smaller than the ones in the neck, but they have been ''shifted'' to an area that is covered by clothing.…”
Section: Extracervical ''Scarless'' Access To the Thyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have described totally endoscopic approaches to the thyroid compartment [88][89][90][91][92][93][94]. Early totally endoscopic approaches described by Ikeda and colleagues [88] used three ports located in the axillary region with low-pressure insufflation.…”
Section: Endoscopic Techniquesmentioning
confidence: 98%
“…Endoscopic techniques evolved first in the field of parathyroid surgery [1 • ]. Significant improvements in endoscopic instrumentation, preoperative localization studies, and the increased understanding of the endoscopic cervical anatomy have facilitated the further growth of head and neck endoscopic surgery for the management of thyroid and parathyroid disease [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%